Structure, function and biology of tissue factor pathway inhibitor-2 - Chand, Hitendra S.; Foster, Donald C.; Kisiel, Walter (Thrombosis and Haemostasis, 2005)
Tissue factor pathway inhibitor-2 (TFPI-2) is a 32 kDa matrix-associated Kunitz-type serine proteinase inhibitor consisting of a short amino-terminal region, three tandem Kunitz-type domains and a positively charged carboxy-terminal tail. Human TFPI-2, previously designated as placental protein 5, inhibits a broad spectrum of serine proteinases almost exclusively through its first Kunitz-type domain, and is thought to play an important role in the regulation of extracellular matrix digestion and re-modeling. In this context, reduced synthesis of TFPI-2 has been related to numerous pathophysiological processes such as inflammation, angiogenesis, atherosclerosis, retinal degeneration and tumor growth/metastasis. In this review, we document current information regarding the expression of TFPI-2 by various tissues, its inhibitory activity and proteinase specificity in-vitro, and discuss possible physiological roles for this inhibitor based on in-vivo studies.
Keywords: Tissue factor pathway inhibitor-2; tumor; metastasis; mutagenesis; X-ray crystallographys